The Role of Food Security in the Incident of Stunting in Toddlers - Dicky Permana Putra; Anita Riantina; Bella Nurindalia; Juniarti; Tharisya Ayu Kirana; Dwi Irma Mayang; Haerawati Idris; Rostika Flora; Misnaniarti; Hamzah Hasyim (HM Publisher, 2023)
Food security has a direct impact on the nutritional intake received by children. When a community or country is unable to ensure a consistent supply of nutritious food, children become vulnerable to deficiencies in essential nutrients needed for their growth and development. This can cause stunting if not treated properly. This study aimed to present the role of food security in the incidence of stunting in toddlers. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the role of food security on the incidence of stunting in toddlers. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Food security plays a key role in preventing stunting in children. This includes the availability of sufficient and nutritious food, fair access to food, food security, food diversification, good environmental sanitation, support for farmers, nutrition education, and public awareness about nutritious food. In order to prevent stunting, it is important to ensure that children have adequate access to nutrient-rich and safe food, as well as to educate the public about the importance of good nutrition. With this comprehensive effort, we can create an environment that supports healthy growth and development in children and reduces stunting rates in communities.